Accidental release of chlorine from storage facility and on-site emergency response plan: a case study at Sungai Dua Penang: article - Anuwar, Nur Afiqah; Abdul Rashid, Zulkifli (2017)
Accidental release of chlorine gas from the storage facility can lead to emergency and endangered the community and environment due to the large amount of chlorine stored in the warehouse. Classified as a highly toxic chemicals, chlorine pose severe hazards when contacting the human body. High exposure to chlorine gas can eventually lead to deaths and injuries. An effective and suitable emergency response plan is therefore required to minimize the adverse effects of the gas leakage to the public and environment. This research investigated three previous case study related to the accidental release of chlorine all around the world. The background and the chronology of the accidents were thoroughly studied to identify the root causes that lead to the accidents. Besides, various example of emergency response plan for chemical process industries were studied and being compared to determine the key elements of an effective emergency response plan proposed for the case study at Sg. Dua water treatment plant.